Predictive value of circulating PD-1hiCXCR5− peripheral T helper cells in systemic inflammatory response syndrome after percutaneous nephrolithotomy - Liu, Zhenyu; Zhu, Wei; Yu, Wentao; Zhou, Yu; Dai, Xiaojing; Wang, Yan; Yu, Jingxuan; Wang, Lin; Niu, Yanbin; Yang, Ling; Xie, Sen; Long, Ping; et al. (Frontiers in Medicine, 2025)
PurposeThe principal objective of this study was to investigate the potential risk factors contributing to the development of postoperative systemic inflammatory response syndrome (SIRS) after percutaneous nephrolithotomy (PCNL), with a key focus on a novel subpopulation of PD-1hiCXCR5−CD4+ T cells, termed peripheral T helper (Tph) cells.MethodsA comprehensive retrospective analysis was undertaken on 399 patients with kidney stones who underwent PCNL at two hospitals between January 2022 and December 2023. The core outcome of interest was the occurrence of post-PCNL SIRS. Univariate and multivariate logistic regression analysis were performed to elucidate independent risk factors for post-PCNL SIRS. A precise nomogram was constructed, integrating the independent risk factors, including Tph cell levels, and receiver operating characteristic (ROC) curves and calibration curves were generated.ResultsAmong the patients, 142 (35.59%) developed post-PCNL SIRS. Univariate analysis highlighted eight potential risk factors. Notably, multivariate analysis identified five independent risk factors for post-PCNL SIRS: high stone density (odds ratio [OR], 5.96; p < 0.001), prolonged operation time (OR, 2.26; p = 0.005), absence of hydronephrosis (OR, 0.37; p < 0.001), positive urine detection for bacteria (OR, 2.13; p = 0.003) and low percentage of circulating Tph cells (OR, 0.39; p < 0.001).ConclusionPatients presenting with low circulating Tph cell levels, high stone density, prolonged operation time, absence of hydronephrosis, and positive urine bacteria are at an elevated risk of developing post-PCNL SIRS. For these individuals, careful consideration of preoperative evaluations, heightened vigilance, and appropriate treatment strategies are essential.